Penentuan Diagnostic Reference Level Pemeriksaan Thoraks Postero-anterior (PA) dengan Klinis Tuberkulosis - Muhammad Irsal; Shinta Gunawati Sutoro; Saifudin; Rizki Amalia (Jurnal Teori dan Aplikasi Fisika, 2025)
Diagnostic reference level (DRL) based on clinical indication of tuberculosis (TB) in chest postero-anterior (PA) examination is still rare. Therefore, this study is expected to be used as an indicator of radiation dose in the optimization protocol. The research method was retrospective, based on the data of chest PA examination exposure parameters of TB clinical and non-TB clinical patients. The study was conducted in June-October 2024 at Hospital A for clinical TB patients, Hospital B, and Hospital C for non-TB patients. Data on exposure parameters were collected and analyzed with descriptive statistics, determination of DRL values was based on the calculation of quartile-2 values, then the DRL value of PA thoracic examination for clinical indications of TB will be compared with the Indonesian national DRL value. The results showed that the DRL value for clinical indications of TB was 0.3 mGy, which is lower than the Indonesian national DRL value. In the future, the determination of the DRL value is based on clinical indications so that the optimization protocol is adjusted to the image quality and the required radiation dose so that the diagnosis will be more accurate and prevent patients from unnecessary exposure. Keywords: Diagnostic reference level (DRL), Chest postero-anterior (PA) examination, Tuberculosis (TB).